An Alternative Non-Cooperative Transmission Scheme Based on Coded Redundant Information - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2017)
Some of the future wireless networks are related to the provision of higher data rates and lower energy consumption. In contrast to the clear increasing spectrum demand, bandwidth is a limited resource. Cooperative diversity allows to increase the spectral efficiency and the reliability of the communication. However, in scenarios with high node density and high mobile data traffic volume the collaboration between multiple nodes can be a huge challenge. In this paper we focus on cognitive radio scenarios in which the users are only allowed to transmit with a limited power and have few opportunities to access the medium. Then, we propose an alternative non-cooperative transmission scheme based on coded redundant information through which users can automatically revert back, when cooperation is not possible. The results indicate that the proposed method outperforms direct transmission and simple repetition schemes, in terms of reliability, as well as spectral and energy efficiency. © 2017 IEEE.